Endovascular Treatment of Large or Giant Non-saccular Vertebrobasilar Aneurysms: Pipeline Embolization Devices Versus Conventional Stents - Wang, Jiejun; Jia, Luqiong; Duan, Zhibin; Wang, Zhongxiao; Yang, Xinjian; Zhang, Yisen; Lv, Ming (Frontiers in Neuroscience, 2019)
Abstract Background: Endovascular treatment of large or giant vertebrobasilar aneurysms (VBAs) using conventional stents is challenging and has unsatisfactory outcomes. Object: This study was performed to retrospectively analyze the efficacy and safety of a flow diverter in the treatment of large and giant VBAs. Methods: We identified 78 patients with 83 large or giant VBAs who accepted endovascular treatment with a Pipeline embolization device (PED) or conventional stent from January 2014 to June 2018. The technical feasibility of the procedure, procedure-related complications, angiographic results, and clinical outcomes were evaluated. Results: Forty-two patients (53.8%, 42/78) with 44 aneurysms (53.0%, 44/83) underwent endovascular treatment with PEDs. Thirty-six patients (46.2%, 36/78) with 39 aneurysms (47.0%, 39/83) underwent endovascular treatment with conventional stents. The complication rate in the PED group and conventional stent group was 7.1% (3/42) and 5.6% (2/36), respectively (odds ratio, 0.765; 95% confidence interval, 0.121–4.851; P = 0.776). During a median follow-up time of 28.8 months, the complete occlusion rate in the PED group and conventional stent group was 90.2% (37/41) and 70.3% (26/37), respectively (odds ratio, 3.913; 95% confidence interval, 1.122–13.652; P = 0.032). Conclusions: Endovascular treatment with a PED is a promising and safe modality for large and giant VBAs, and the complication rate is acceptable, comparing with conventional endovascular treatment.